WSN – An Emerging Technology and its Security Meaures - Abidin, Shafiqul (International Journal of Computer Sciences and Engineering, 2018)
Wireless Sensor Network (WSN) is one of the merging network technologies. It is an extensively distributed network equipped with low powered and lightweight wireless sensor nodes. WSN are being deployed to monitor system and environment. WSN are being used in health sectors, military operations, automation industries, traffic monitoring, oil refineries etc. But with the emerging applications, WSN is prone to attacks and threats. These attacks and threats must be studied thoroughly in order to counter them. Today security issues are the major challenges faced by WSN. The deployment of wireless sensor nodes in hostile environments makes them the subject of lethal attacks, also due to the limitations of resources processing capability, power consumption & communication range WSN are vulnerable to many types of threats/attacks. There are serious consequences if security of WSN gets compromised by any means such as information theft, lack of privacy, etc. Thus it must be our utmost priority to save WSNs from malicious attacks. In this study we have highlighted the various fatal attacks that can destruct WSN with their impacts and consequences.